IMPLEMENTASI PENJUALAN BERBASIS WEB PADA USAHA PRELOVED SECOND WEAR UNTUK MENINGKATKAN AKSESIBILITAS PELANGGAN - Anindhita Azzahra; Hanif Annaufal; Rahma Hanum (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
The web-based sales system for Second Wear aims to make it easier for customers to buy and sell second-hand items. The website has a simple and user friendly design, allowing customers to explore its features with ease, while also including security features for transactions and a review system to help build trust among users. With this approach, Second Wear creates a safe and welcoming environment, which is expected to increase customer participation and sales in the preloved fashion market.